The sociocognitive dimension of hate speech in readers' comments on Serbian news websites. (March 2020) - Đorđević, Jasmina P.
Abstract: Comment sections on news websites bear no immediate threat of sanctions and users feel free to express open criticism or insult. Other than causing offense and undermining the dignity of readers with a different opinion, a rather dangerous outcome of hate speech is that it affects the sociocognitive interface between discourse and society in the sense that it has a negative impact on the readers' cognitive notions of information, beliefs and knowledge. Based on the analytical approach proposed in Sociocognitive Discourse Studies, the study examines 939 comments posted in the comment section of the Serbian news website Politika. Besides confirming that hate speech in the readers' comments is a rather frequent means of establishing a communicative Common Ground among news readers, the analysis shows that hate speech is a reflection of the negative impact of news on the sociocognitive interface between discourse and society. The research also demonstrates that Sociocognitive Discourse Studies may be applied to the analysis of readers' comments as a specific type of written discourse that reflects the mental models news readers create when exposed to media discourse.